2020
DOI: 10.3390/molecules25133091
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus sajor-caju-Mediated Synthesis of Silver and Gold Nanoparticles Active against Colon Cancer Cell Lines: A New Era of Herbonanoceutics

Abstract: Herbal medicines are widely used worldwide and much appreciated because of their fewer side effects and the ability to fight diseases at the root cause. Active ‘phyto’ ingredients require a scientific approach and a mechanism to distribute components at the target site for better therapeutic results. Nanotechnology, on the other hand, has created new hope for cancer treatment but is still far from being proven in clinical settings. This article combines a unique approach to synthesis with the use of Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 49 publications
1
26
0
2
Order By: Relevance
“…The silver element composition in AgNPs was confirmed by EDX, revealing a major peak at around 3 keV [ 22 ]. From Dynamic Light Scattering (DLS) measurement, we found that the hydrodynamic diameter of AgNPs was greater than the average size observed from TEM due to the solvent and stabilizer layers present around the AgNPs’ surface [ 34 ]. The negative zeta potential of −43.9 mV ( Figure 2 b) proved the high stability of AgNPs due to the electrostatic repulsion of NPs in the solution [ 24 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The silver element composition in AgNPs was confirmed by EDX, revealing a major peak at around 3 keV [ 22 ]. From Dynamic Light Scattering (DLS) measurement, we found that the hydrodynamic diameter of AgNPs was greater than the average size observed from TEM due to the solvent and stabilizer layers present around the AgNPs’ surface [ 34 ]. The negative zeta potential of −43.9 mV ( Figure 2 b) proved the high stability of AgNPs due to the electrostatic repulsion of NPs in the solution [ 24 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic and pro-apoptotic effects of L. sajorcaju extracts were demonstrated by Finimundy et al: the extract decreased the viability of HCT-116 cells, induced apoptosis, and affected the cell cycle, leading to its arrest in the G2/M phase [50]. Chaturvedi et al reported similar results revealing cytotoxic and pro-apoptotic effects of PSC water extract on HCT-116 cells [51]. The fungus was studied on other models, as well, and was shown to affect human cervical cancer HEp-2 and HeLa cells [47], breast cancer MCF-7 and non-small cell lung cancer NCI-H460 cells [48], and human gastric cancer (AGS) and hepatocellular carcinoma cells (HepG2) [49].…”
Section: Discussionmentioning
confidence: 73%
“…At dilutions ranging from 10 to 30 g mL −1 , AuNPs derived from Pleurotus florida extract by photo-irradiation demonstrated dose-dependent antiproliferative activity against various cancer cell lines (A-549, K-562, HeLa and MDA-MB) [109]. Chaturvedi et al [110] investigated cytotoxicity and observed that AgNPs and AuNPs formed by Pleurotus sajor-caju extract (PS) were effective against the HCT-116 cancer cell line. HCT-116 cancer cell viability was inhibited by P. sajor-caju extract, AuNPs and AgNPs, with IC 50 values of 60, 80 and 50 g mL −1 , respectively.…”
Section: Edible Mushrooms Derived Nanoparticles (Nps)mentioning
confidence: 99%